Penulisan Judul Skripsi bagi Pemula, Kajian Masalah Empirik dalam Memberikan Penelitian bagi Mahasiswa FAI UNISMA Bekasi - Yayat Suharyat (Turats, 2015)
In this article explained that the students problems that often become obstacles in doing the writing (scientific papers) is not just a question of the scope of educational material that is still not qualified, but also due to the lack of skills in methodological factors. Early identification of problems in the writing of student thesis can be identified through the analysis of input-process-output. Each comprehensive study requires precise objectives and strategies, so as to gain confidence to implement it. So with the policies and standards of good management, each direction of the development of any subject including Research Methods in Higher Education will obtain maximum results. Need to find a way out for all of these conditions, namely by offering another approach and other study material in the study of Islamic education at the university.